PENGARUH BEBAN KERJA, KEMAMPUAN KOMUNIKASI DAN KETERAMPILAN KERJA TERHADAP KINERJA PENYULUH PERTANIAN KAB. SERDANG BEDAGAI - Ayuna Niken Pratiwi; Suwito .; Sugi Arto Pujungkoro (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2015)
The implementing body extension and food security (BP2KP) Serdang Bedagairegencies a unit supporting the implementation of agricultural extension. Thedevelopment of farmer groups showed no growth both in quantity and quality. Thedecline in the performance of technicians are also seen in some instances the duties andobligations of extension itself as administrative duties. Anailisis of the results showed that44.5% of agricultural extension performance is affected by the workload, communicationskills and work skills, while 55.5% is influenced by other variables outside variablesused in this paper. Variable workload, communication skills, and skills to work togethersignificant effect terahadap peyuluhan performance of agriculture (BP2KP) SerdangBedagai regencies.Keywords: Beban Kerja, Kemampuan Komunikasi, Keterampilan Kerja, KinerjaPenyuluh Pertanian.